2022
DOI: 10.1038/s41388-022-02205-0
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4 biology in alveolar rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children and phenocopies a muscle precursor that fails to undergo terminal differentiation. The alveolar subtype (ARMS) has the poorest prognosis and represents the greatest unmet medical need for RMS. Emerging evidence supports the role of epigenetic dysregulation in RMS. Here we show that SMARCA4/BRG1, an ATP-dependent chromatin remodeling enzyme of the SWI/SNF complex, is prominently expressed in primary tumors from ARMS patients and cell cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In contrast to the non-degrader form of ACBI1, which had no anti-cancer effect, the ACBI1 PROTAC killed SMARCA4-dependent leukemia cells as well as SWI/SNF-deficient cancer cells that are dependent on residual SWI/SNF activity. ACBI1 also compromised the growth of alveolar rhabdomyosarcoma tumors harboring the PAX3:FOX01 oncogene, demonstrating its anti-cancer effects in vivo [170].…”
Section: Targeting Swi/snf Family VIII Bromodomainsmentioning
confidence: 93%
“…In contrast to the non-degrader form of ACBI1, which had no anti-cancer effect, the ACBI1 PROTAC killed SMARCA4-dependent leukemia cells as well as SWI/SNF-deficient cancer cells that are dependent on residual SWI/SNF activity. ACBI1 also compromised the growth of alveolar rhabdomyosarcoma tumors harboring the PAX3:FOX01 oncogene, demonstrating its anti-cancer effects in vivo [170].…”
Section: Targeting Swi/snf Family VIII Bromodomainsmentioning
confidence: 93%
“…Moreover, the SWI/SNF complex and the PRC2 complex containing EZH2 methyltransferase have been shown antagonistic activity in gene transcription ( 104 , 105 ), of which EZH2 has an obvious anti-tumor effect on cell lines and xenografts with concurrent loss of SMARCA2 and SMARCA4 ( 106 , 107 ). Dual loss of SMARCA4 and SMARCA2 also impacts tumor cell growth in PAX3:FOXO1+ARMS ( 108 ).…”
Section: Genetic Combination and Mechanism Of Paralog-based Slmentioning
confidence: 99%
“…However, other strategies have been explored, including the targeting of pathways associated with PAX::FOXO1 stability or expression, targeting its transcriptional co-activators or targeting down-stream signaling pathways as previously reviewed [4,5]. Genome-scale CRISPR/Cas9 targeting of epigenetic genes and subsequent validation studies revealed the wild type ATP-dependent chromatin remodeling enzyme SMARCA4 as a crucial vulnerability for the survival of both human fusion-positive alveolar and fusion-negative embryonal rhabdomyosarcoma cells [129,131,132]. SMARCA4 and its paralogue SMARCA2 act as catalytic ATPase subunits of the SWI/SNF complexes, including BAF, PBAF and ncBAF, representing fundamental epigenetic regulators of gene transcription [133].…”
Section: Enhancing Target Selectivity To Smarca4/a2 In Rhabdomyosarcomamentioning
confidence: 99%
“…SMARCA4 and its paralogue SMARCA2 act as catalytic ATPase subunits of the SWI/SNF complexes, including BAF, PBAF and ncBAF, representing fundamental epigenetic regulators of gene transcription [133]. In both fusion-positive and fusion-negative cells, in vitro experiments using siRNA, shRNA, or CRISPR-mediated sgRNA SMARCA4 knockdown approaches showed that SMARCA4 loss reduces cell proliferation, anchorage-dependent clonogenicity, and activates myogenic differentiation [129,131,132]. Mechanistically, in fusion-positive cells, SMARCA4 shares a spatial proximity with PAX3::FOXO1 on chromatin even if PAX3::FOXO1 is not incorporated into stable SWI/SNF complexes [129].…”
Section: Enhancing Target Selectivity To Smarca4/a2 In Rhabdomyosarcomamentioning
confidence: 99%